PENGARUH PARTISIPASI AKTIF MASYARAKAT DAN KUALITAS PELAYANAN PUBLIK TERHADAP PENGELOLAAN DANA DESA PADA DESA SE-KECAMATAN PERCUT SEI TUAN - Maya Sari Br Saragih; Muhammad Ridha Habibi; Nisha Marina; ok Hidayat; Taufik Hidayat (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
This research was motivated by the importance of firm value as an indicator of performance and investment attractiveness in the Indonesian capital market. Firm value is influenced by several factors, particularly ownership structure and profitability, which reflect the company’s ability to generate returns. The purpose of this study was to empirically examine the effects of managerial ownership, institutional ownership, foreign ownership, and profitability on firm value. The data were collected through documentation methods using audited annual financial reports published by companies listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling, and the analysis was carried out through multiple linear regression as a quantitative approach. The findings revealed that managerial ownership had no significant effect on firm value, suggesting that managers holding shares did not necessarily align their interests with those of other shareholders. In contrast, institutional ownership and foreign ownership had a positive and significant impact on firm value, indicating that external monitoring by institutional and foreign investors enhanced transparency and managerial efficiency. Profitability, proxied by Return on Equity (ROE), also showed a significant positive effect on firm value, confirming that strong financial performance is a major determinant in attracting investors. Overall, the study emphasized that ownership structure and profitability are critical determinants of firm value. The practical implication is that improving profitability and encouraging greater involvement of institutional and foreign investors can serve as effective strategies to enhance competitiveness and firm value in the Indonesian capital market.